Multivariate Recurrent Events in the Presence of Multivariate Informative Censoring with Applications to Bleeding and Transfusion Events in Myelodyplastic Syndrome - Zeng, Donglin (2014)
We propose a general novel class of joint models to analyze recurrent events that has a wide variety of applications. The application of focus on this paper is to model the bleeding and transfusion events in Myelodyplastic Syndrome (MDS) studies, where patients may die or withdraw from the study early due to adverse events or other reasons, such as consent withdrawal or required alternative therapy during the study. The proposed model accommodates multiple recurrent events and multivariate informative censoring through a shared random effects model. The random effects model captures both within-subject and within-event dependence simultaneously. We construct the likelihood function for the semi-parametric joint model and develop an EM algorithm for inference. The computational burden does not increase with the number of types of recurrent events. We utilize the MDS clinical trial data to illustrate our proposed methodology. We also conduct a number of simulations to examine the performance of the proposed model.